Selectivity Control of C-O Bond Cleavage for Catalytic Biomass Valorization - Jian, Yumei; Meng, Ye; Li, Hu (Frontiers in Energy Research, 2022)
Increasing fossil fuels consumption and global warming have driven the global revolution towards renewable energy sources. Lignocellulosic biomass is the main source of renewable carbon-based fuels. The abundant intermolecular linkages and high oxygen content between cellulose, hemicellulose, and lignin limit the use of traditional fuels. Therefore, it is a promising strategy to break the above linkages and remove oxygen by selective catalytic cracking of C–O bond to further transform the main components of biomass into small molecular products. This mini-review discusses the significance of selectivity control in C–O bond cleavage with well-tailored catalytic systems or strategies for furnishing biofuels and value-added chemicals of high efficiency from lignocellulosic biomass. The current challenges and future opportunities of converting lignocellulose biomass into high-value chemicals are also summarized and analyzed.